Relevansi Teori Belajar Konstruktivisme dengan Model Inkuiri Terbimbing terhadap Hasil Belajar Siswa - Pande Made Aditya Pramana; Ni Ketut Suarni; I Gede Margunayasa (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This study explores the relationship between constructivist learning theory and the application of guided inquiry models to the achievement of student learning outcomes at the secondary education level. Literature methods are used to analyze various sources that elaborate the principles of constructivism as well as the implementation of guided inquiry models in learning contexts. By integrating constructivist theory that emphasizes students' active learning through the construction of their own knowledge with a guided inquiry approach that provides structure and guidance, the study highlights its relevance and impact on student learning outcomes. In-depth analysis of the relevant literature provides in-depth insights into possible improvements in learning outcomes through the application of collaboration between constructivism theory and guided inquiry models in formal educational contexts. The practical implications of the integration of these two approaches are also discussed in order to improve the effectiveness of learning in educational environments. It can be concluded that the integration between constructivist learning theory and guided inquiry models can be a relevant and useful approach in improving the quality of education.